Immunotherapeutic Blockade of CD47 Increases Virus Neutralization Antibodies - Lamin B. Cham; Thamer A. Hamdan; Hilal Bhat; Bello Sirajo; Murtaza Ali; Khaled Saeed Tabbara; Eman Farid; Mohamed-Ridha Barbouche; Tom Adomati (Vaccines)
Background/Objectives: CD47 is a cell surface glycoprotein moderately expressed in healthy cells and upregulated in cancer and viral infected cells. CD47’s interaction with signal regulatory protein alpha (SIRPα) inhibits phagocytic cells and its interaction with thrombospondin-1 inhibits T cell response. Experimental evidence has revealed that the blockade of CD47 resulted in the increased activation and function of both innate and adaptive immune cells, therefore exerting antitumoral and antiviral effects. Recent studies have shown that the combination of vaccines and immune checkpoint inhibitors could be a promising approach to increasing vaccine immunogenicity. Here, we investigated the vaccinal effect of anti-CD47 antibodies and discussed the possibilities of combining anti-CD47 treatments with vaccines. Methods: Using vesicular stomatitis virus (VSV), a widely used replication-competent vaccine vector, we evaluated the impact of the immunotherapeutic blockade of CD47 on cellular, humoral, and protective immunity. We infected C57BL/6 mice with VSV, treated them with anti-CD47 antibodies or an isotype, and evaluated the total immunoglobulin (Ig), IgG neutralizing antibodies, B cell activation, CD8+ T cell effector function, and survival of the mice. Results: We found that the treatments of anti-CD47 antibodies led to significantly increased Ig and IgG neutralizing antibody levels compared to the isotype treatment. Flow cytometric analysis of B cells revealed no difference in the number of circulating B cells; however, we observed an increased surface expression of CD80 and CD86 in B cells among anti-CD47-treated mice. Further analysis of the impact of CD47 blockade on T immunity revealed a significantly higher percentage of IFN-γ+ CD4 and IFN-γ+ CD8 T cells in anti-CD47-treated mice. Upon infecting mice with a lethal VSV dose, we observed a significantly higher survival rate among the anti-CD47-treated mice compared to control mice. Conclusions: Our results indicate that anti-CD47 treatment induces a stronger cellular and humoral immune response, leading to better protection. As such, immunotherapy by CD47 blockade in combination with vaccines could be a promising approach to improve vaccine efficacy.